GUEST HOUSE HUMA BETANG INDAH DI BUNTOK - Wanagita, Yuztira; Hadinata, Irwan Yudha (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Guest house is a building built for accommodation purposes. The main problem in designing the Huma Betang Indah Guest House in Buntok is how the building can harmonize with nature through dayak culture which is comfortable for the guest. With the direct analogy approach as a design method, the design of this guest house has an object of observation in the form of a rumah betang. Rumah betang is a traditional Dayak tribe house that has strong ties with nature. Thus to apply the principles of rumah betang to the guest house the concept of Analogy architecture is used. A guest house that can provide new experiences for guests by providing various natural elements in it.